Kronik tromboembolik pulmoner hipertansiyon nedeniyle uygulanan iki taraflı pulmoner tromboendarterektomi: Bölgemizdeki en küçük olgu - (:unkn) unknown (My University, 2013)
Hidrosefali tedavisi için ventriküloatriyal (VA) şantla- rın kullanılması kronik tromboembolik pulmoner hipertansi- yon (KTEPH) gelişimi ile birliktedir. Kronik tromboembolik pulmoner hipertansiyon kronik veya tekrarlayan emboliler sonrası gelişir. Çocuklarda nadir görülmekle birlikte tahrip edici potansiyeli yüksektir. Pulmoner tromboendarterektomi (PTE) KTEPH’li hastalarda önemli ve iyileştici bir tedavi yön- temidir. Bu yazıda, VA şant işlemi sonrası KTEPH gelişen 14 yaşında bir erkek olgu sunuldu. Hastada başarılı PTE sonrasında sistolik pulmoner arter basıncı 75 mmHg’den 30 mmHg’ye geriledi. Çocukluk çağı KTEPH’de PTE’yi öneri- yoruz.

The insertion of ventriculoatrial (VA) shunts for the treatment of hydrocephalus is associated with the development of chronic thromboembolic pulmonary hypertension (CTEPH). Chronic thromboembolic pulmonary hypertension occurs in patients with recurrent or chronic pulmonary embolism, and is a rare but, potentially devastating disease in children. Pulmo- nary thromboendarterectomy (PTE) is an important curative therapy for patients with CTEPH. Herein, we present a case of a 14 year-old male patient with CTEPH that developed after a VA shunt procedure. After successful PTE, systolic pulmonary artery pressure was decreased from 75 mmHg to 30 mmHg. PTE is recommended in the pediatric CTEPH population.
Bilateral pulmonary thromboendarterectomy for chronic thromboembolic pulmonary hypertension: The youngest case in our region
Keywords: Kalp ve Kalp Damar Sistemi; Pediatri